2020
DOI: 10.1099/ijsem.0.004204
|View full text |Cite
|
Sign up to set email alerts
|

Parapseudoflavitalea muciniphila gen. nov., sp. nov., a member of the family Chitinophagaceae isolated from a human peritoneal tumour and reclassification of Pseudobacter ginsenosidimutans as Pseudoflavitalea ginsenosidimutans comb. nov.

Abstract: A Gram-stain-negative, microaerophilic, non-motile, rod-shaped bacterium strain designated PMP191FT, was isolated from a human peritoneal tumour. Phylogenetic analysis based on 16S rRNA gene sequences indicated that the organism formed a lineage within the family Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Even though chemotaxonomic procedures marked a turning point in prokaryotic systematics (Goodfellow et al, 2012), results can be influenced by cultivation conditions (i.e., fatty acid analysis) or by inexperienced staff (i.e., regarding the interpretation of polar lipids patterns on 2-D TLC plates; Sutcliffe et al, 2013). In favour of a revitalization of bacterial taxonomy, in silico chemotaxonomic analyses were already used in some studies to complement and, in some cases, replace characteristics traditionally determined in the laboratory (Amaral et al, 2014;Fotedar et al, 2020;10.3389/fmicb.2022.975365 Frontiers in Microbiology 13 frontiersin.org Lawson et al, 2020). Here, we attempted to determine in silico cell-wall peptidoglycan, respiratory quinone, fatty acids and polar lipid patterns of Geodermatophilaceae.…”
Section: Final Remarks and Taxonomic Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though chemotaxonomic procedures marked a turning point in prokaryotic systematics (Goodfellow et al, 2012), results can be influenced by cultivation conditions (i.e., fatty acid analysis) or by inexperienced staff (i.e., regarding the interpretation of polar lipids patterns on 2-D TLC plates; Sutcliffe et al, 2013). In favour of a revitalization of bacterial taxonomy, in silico chemotaxonomic analyses were already used in some studies to complement and, in some cases, replace characteristics traditionally determined in the laboratory (Amaral et al, 2014;Fotedar et al, 2020;10.3389/fmicb.2022.975365 Frontiers in Microbiology 13 frontiersin.org Lawson et al, 2020). Here, we attempted to determine in silico cell-wall peptidoglycan, respiratory quinone, fatty acids and polar lipid patterns of Geodermatophilaceae.…”
Section: Final Remarks and Taxonomic Consequencesmentioning
confidence: 99%
“…Laboratory-based DNA–DNA hybridisation methods have already been routinely replaced by overall genome relatedness indices (OGRI; Chun et al, 2018 ) of which digital DNA:DNA hybridization was shown to be the best-performing method ( Meier-Kolthoff et al, 2013a ). The use of in silico analysis for chemotaxonomic traits is now being introduced to replace characteristics traditionally determined in the laboratory ( Amaral et al, 2014 ; Fotedar et al, 2020 ; Lawson et al, 2020 ) with the dual goal of both increasing the speed of the description of taxa and the accuracy and consistency of taxonomic reports ( Chun and Rainey, 2014 ; Whitman, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Members of this family are Gramstain-negative, usually non-motile, rod-shaped, aerobic or facultative anaerobic and contain MK-7 as the predominant respiratory ubiquinone [1][2][3][4][5][6]. At the time of writing, the family Chitinophagaceae was composed of 44 genera with validly published names (https://lpsn.dsmz.de/family/chitinophagaceae) and was supplemented with Agriterribacter [2], Parapseudoflavitalea [3], Limnovirga [4], Phnomibacter [5] and Pinibacter [6] in the past 2 years. Species in this family usually possess various functions in the environment [7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The family Chitinophagaceae , belonging to the phylum Bacteroidota, was proposed by Kämpfer et al [1] and incorporated several genera on the basis of 16S rRNA gene sequence analyses and some phenotypic similarities. Members of this family are Gram-stain-negative, usually non-motile, rod-shaped, aerobic or facultative anaerobic and contain MK-7 as the predominant respiratory ubiquinone [1–6]. At the time of writing, the family Chitinophagaceae was composed of 44 genera with validly published names (https://lpsn.dsmz.de/family/chitinophagaceae) and was supplemented with Agriterribacter [2], Parapseudoflavitalea [3], Limnovirga [4], Phnomibacter [5] and Pinibacter [6] in the past 2 years.…”
Section: Introductionmentioning
confidence: 99%